(untitled) (Jurnal Ipteks Terapan, 2024)
The spine is considered one of the important imaging parts of the body in all age groups.. In the event of damage to the spine, the entire body will be affected, and a high concentration of nerves will cause excruciating pain. In this study the data were obtained using a CT scan (Computed Tomography scan). In this study took 5 images of the spine from a CT scan and processed into 40 images. In this work, restoration is to restore an image that has degraded the quality of impulse and gausian noise. From the results of the implementation and analysis of the results of image processing restoration. Over time, a number of images spatially, it can be concluded that the image that has been restored with the average filter and the median filter performed on the spine Computed Tomography Scan image. In the test image restoration results showed the image of impulse noise filter median kernel 3x3 well and maximally shown with MSE 4.25383 and PSNR 41.877 while gausian noise image less can be restored with an average gausian filter 5 × 5 with MSE 7.36876 and PSNR 39.4909